EXISTENCE OF SOLUTIONS FOR FRACTIONAL INTEGRO-DIFFERENTIAL EQUATIONS INVOLVING THE CAPUTO TYPE ATANGANA-BALEANU DERIVATIVE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The existence and uniqueness of solutions for FNIDE in the idea of Atangana-Baleanu derivative inBanach spaces are investigated in this research. In this case, the FD is taken in the Caputo sense. The Banach andKrasnoselskii-Schaefer FPT are used to show the desired results.